A Model for Determining Appropriate Speed Breaker Mechanism for Power Generation - Ikuobase Emovon (Journal of Applied Science & Process Engineering, 2018)
The key to sustainable economic development is having adequate electricity to power homes and industrial machines. However, electric power supply in majority of developing countries is grossly inadequate. To improve on the power generation different renewable energy sources have been explored. One of the sources of renewable energy is the application of speed breaker system to convert kinetic energy of moving vehicles into electricity using various mechanisms. The purpose of this paper is to develop a methodology for determining the most appropriate mechanism of speed breaker system for effective power generation. The proposed approach aggregated the AHP and the WASPAS methods. The efficacy of the methodology is illustrated with a numerical example. From the analysis, the optimum speed breaker mechanism for power generation is the roller mechanism. A sensitivity analysis was also carried out to determine the effect of one of the parameters of the proposed method on the performance of the different mechanisms. The result of the sensitivity analysis showed that the optimum solution remained unchanged.